2016
DOI: 10.1159/000452895
|View full text |Cite
|
Sign up to set email alerts
|

Khat (<b><i>Catha edulis</i></b>) and Obesity: A Scoping Review of Animal and Human Studies

Abstract: Background: Khat (Catha edulis) is a plant that is deeply rooted in the cultural life of East African and Southwestern Arabian populations. Prevalent traditional beliefs about khat are that the plant has an effect on appetite and body weight. Summary: This review assesses the accumulated evidences on the mutual influence of monoamines, hormones and neuropeptides that are linked to obesity. A few anti-obesity drugs that exert their mechanisms of action through monoamines are briefly discussed to support the not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 102 publications
(117 reference statements)
1
18
0
Order By: Relevance
“…It has been suggested that this use pattern inhibits work productivity and leads to financial problems . Items grouped in weight control were consistent with appetite suppressant effects of cathinone, one of the main ingredients of khat . Finally, family issues included items that describe unfavourable views toward khat use among women.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that this use pattern inhibits work productivity and leads to financial problems . Items grouped in weight control were consistent with appetite suppressant effects of cathinone, one of the main ingredients of khat . Finally, family issues included items that describe unfavourable views toward khat use among women.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, this result was inconsistent with the results of the other regional and international studies reporting that obesity is one of the most risk factors of dyslipidaemia 19 , 20 . Qat results in anorexia after qat consumption due to the inhibitory effects of cathinone and cathine on the appetite centre in the hypothalamus 21 . However, obesity was also not observed in non-qat chewers, suggesting that obesity was not noted among Yemeni qat and non-qat chewers.…”
Section: Discussionmentioning
confidence: 61%
“…Dietary risk behaviours impacting on obesity include the “consumption of energy-dense foods high in sugars and fat” [ 17 , 18 ] and insufficient fruit and vegetable intake [ 19 ]. Engaging in physical activity [ 20 , 21 ], khat [ 22 ] and tobacco use [ 8 , 17 , 18 ] have been found to decrease the likelihood of having overweight and obesity. Obesity is linked with several chronic NCDs such as hypertension and type 2 diabetes [ 3 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%